2022
DOI: 10.3390/s22197414
|View full text |Cite
|
Sign up to set email alerts
|

Research on Wind Power Short-Term Forecasting Method Based on Temporal Convolutional Neural Network and Variational Modal Decomposition

Abstract: Wind energy reserves are large worldwide, but their randomness and volatility hinder wind power development. To promote the utilization of wind energy and improve the accuracy of wind power prediction, we comprehensively consider the influence of wind farm environmental factors and historical power on wind power generation. This paper presents a short-term wind power prediction model based on time convolution neural network (TCN) and variational mode decomposition (VMD). First, due to the non-smooth characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…Liu Hui et al [39] converted traffic flow data into different frequency components using VMD, optimized weights using ICA algorithm, and integrated three prediction models (GMDH, BILSTM, and ELMAN) to predict different modal components. Tang Jingwei et al [40] decomposed environmental variables using VMD and found the most power-relevant modal components based on MIC and Pearson correlation coefficients, predicting them along with historical power data. Cai Changchun et al [41] utilized GRU models to achieve prediction of low frequency components and TCN models to achieve prediction of high frequency components after VMD modal decomposition.…”
Section: Related Workmentioning
confidence: 99%
“…Liu Hui et al [39] converted traffic flow data into different frequency components using VMD, optimized weights using ICA algorithm, and integrated three prediction models (GMDH, BILSTM, and ELMAN) to predict different modal components. Tang Jingwei et al [40] decomposed environmental variables using VMD and found the most power-relevant modal components based on MIC and Pearson correlation coefficients, predicting them along with historical power data. Cai Changchun et al [41] utilized GRU models to achieve prediction of low frequency components and TCN models to achieve prediction of high frequency components after VMD modal decomposition.…”
Section: Related Workmentioning
confidence: 99%
“…TCN is a convolutional neural network specifically designed for analyzing time series data [23][24][25]. It consists of three key components: causal convolution, dilated convolution, and residual connectivity.…”
Section: Time Convolutional Networkmentioning
confidence: 99%
“…Most of these papers proposed models for locations in China, such as [21][22][23][24][25][26][27][28]. Six works proposed models for locations in the USA [29][30][31][32][33][34] and nine works for locations in Europe, such as Spain and Belgium [35][36][37][38][39][40][41][42][43]. Only one work was found that targeted the hot desert climate in which data from a wind farm in Pakistan was used [44].…”
Section: Related Workmentioning
confidence: 99%